2021
DOI: 10.3390/pr9061055
|View full text |Cite
|
Sign up to set email alerts
|

g-C3N4 Sensitized by an Indoline Dye for Photocatalytic H2 Evolution

Abstract: Protonated g-C3N4 (pCN) formed by treating bulk g-C3N4 with an aqueous HCl solution was modified with D149 dye, i.e., 5-[[4[4-(2,2-diphenylethenyl) phenyl]-1,2,3,3a,4,8b-hexahydrocyclopent[b]indol-7-yl] methylene]-2-(3-ethyl-4-oxo-2-thioxo-5-thiazolidinylidene)-4-oxo-thiazolidin-2-ylidenerhodanine, for photocatalytic water splitting (using Pt as a co-catalyst). The D149/pCN-Pt composite showed a much higher rate (2138.2 µmol·h−1·g−1) of H2 production than pCN-Pt (657.0 µmol·h−1·g−1). Through relevant character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Tis indicates that Eosin Y could not be detected on the surface of the composite using SEM. Furthermore, a similar study conducted by Chen and coworkers using g-C 3 N 4 sensitized by indoline dye reported that the TEM images could not detect organic dyes on the surface of a sample [42].…”
Section: Morphology and Chemical Compositionmentioning
confidence: 89%
See 2 more Smart Citations
“…Tis indicates that Eosin Y could not be detected on the surface of the composite using SEM. Furthermore, a similar study conducted by Chen and coworkers using g-C 3 N 4 sensitized by indoline dye reported that the TEM images could not detect organic dyes on the surface of a sample [42].…”
Section: Morphology and Chemical Compositionmentioning
confidence: 89%
“…Te sensitized photocatalyst achieves the best photocatalytic performance at 94.62%. Tis could be explained by the improved charge separation and better light photon harvesting [42]. Similarly, all the composites had signifcantly higher performance than all the pure photocatalysts, and an increase in ZnFe composition was accompanied by an increase in photocatalytic activity.…”
Section: Photocatalytic Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…D149/Protonated g-C3N4 (pCN) Pt Calcination method, 18 mL aqueous solution, 0.81 mg H2PtCl6.6H2O, 2 mL triethanolamine (TEOA), 300WXe lamp, λ>420 nm, 12 °C 2138 μmolg −1 h −1 [135] Pd/2D C3N4 Hydrothermal method, oil bath method for Pd nanotubes preparation, 100 °C, 90 mL water and 10 mL TEOA, 300 W Xe lamp, λ>400 nm 1208.6 μmolg −1 h −1 [136] Co-Pi/Bi-La2Ti2O7 nanosheet/Pt Hydrothermal method, room temperature, methanol 20 vol%, 0.1 M AgNO3, Xe light source, (λ>400 nm)…”
Section: Photocatalystmentioning
confidence: 99%